2001
DOI: 10.1088/0268-1242/16/6/101
|View full text |Cite
|
Sign up to set email alerts
|

Melting temperatures of semiconductor nanocrystals in the mesoscopic size range

Abstract: A model, free of any adjustable parameters, is extended to predict the size dependence of the melting temperature of semiconductor nanocrystals. The model predictions are consistent with the experimental results for Si, Bi and CdS semiconductor nanocrystals. In addition, the simplified model with fixed material constants is in agreement with the usual phenomenological relationship that the size dependence of the melting temperature is proportional to the reciprocal of the nanocrystal radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 15 publications
5
56
0
Order By: Relevance
“…According to Eq. (4) and the related parameters [2,[19][20][21][22] in Table 2, γ i = 2.93 Jm −2 , the value of several joules per meter square is in agreement with the interface energy of a series of the interfaces between the metals and the ceramics [9].…”
Section: Thermodynamics Of Size-dependent Interface Adhesive Energysupporting
confidence: 62%
See 1 more Smart Citation
“…According to Eq. (4) and the related parameters [2,[19][20][21][22] in Table 2, γ i = 2.93 Jm −2 , the value of several joules per meter square is in agreement with the interface energy of a series of the interfaces between the metals and the ceramics [9].…”
Section: Thermodynamics Of Size-dependent Interface Adhesive Energysupporting
confidence: 62%
“…(4). For ZrO 2 , h is calculated by the lattice volume [16], V is calculated by the mass and the density [2], S v = S m -R with the melting entropy S m = H / T m [19], T m is the melting point. For metals, S v = S m .…”
Section: Test Of Interface Binding Strengthmentioning
confidence: 99%
“…The approach favors closely the atomistic model of Jiang and Shi [414] who relate the amplitude of atomic vibration to the melting behavior of a surface and the surface energy. With few adjustable parameters, the model based on Lindemann and Mott premises for the relationship of vibrational melting entropy and melting temperature has applied well to the sizedependent melting of compounds [415], metals [416], nanotubes [417], polymers [418], glasses [419], inert gases [420], ice [421], and semiconductors [422]. In conjunction with Jiang's approach, the current BOLS premise could provide deeper insight into the physical origin and the general trends of the phase transition behavior of a nanometric solid.…”
Section: Other Applicationsmentioning
confidence: 99%
“…As pointed out in the experimental observations for free nanocrystals or epitaxial thin films on inert substrates [134,257], there exist different degrees of spin-spin interactions between inner and surface atoms because of the reduction in the number of spin interactions at the surface with increase of lattice vibration [5,113,12,122,258]. For thin films with strong film/substrate interaction, the vibration of atoms there is depressed.…”
Section: In Order To Interpret T N (D) In a Unified Form T N (D)mentioning
confidence: 99%
“…Over the past decades, following Takagi s experimental pioneering work in 1954 [8], which demonstrated T m (D) < T m ( ) where denotes the bulk size, thermal stabilities of metallic [9], organic [10,11], semiconductor [12] nanocrystals have been intensively studied experimentally and theoretically. It has been revealed that the crystalline lattice spacing in nanocrystals can be altered by surface relaxation [13], stress [14], or strain.…”
Section: Thermal Stability Of Nanocrystalline Magnetic Materialsmentioning
confidence: 99%